The Stubble Burning Problem in Sustainable Agriculture - Yıldırım, Aytül (My University, 2023)
Stubble is the short stalks that remain after harvesting a crop such as wheat. The stubble, which makes up soil organic matter and provides nutrients for soil microorganisms, is important for agricultural production. But farmers are supposed that stubble burning provides convenience in tillage results and reduce diseases and pests, which achieve obtaining higher crop yields, and reduce the economic costs. As the result of burning stubble, soil organic matter is decreased, the soil structure is deteriorated, microbiological activity in the soil is regressed, soil moisture is decreased, the biological balance is deteriorated and the risk of erosion is increased. It is vital to use instruments that mix the stubble under the soil so that it does not interfere with the preparation of the seed bed after the harvest. In regions where there is too much stubble, nitrogen fertilizer should be applied to around 1% of the remaining stalk to ensure that the stubble breaks down and decomposes into organic matter. In this review, the importance of stubble in agricultural production, stubble management, the reasons why farmers burn stubble, the negative effects of stubble burning on the soil fertility and environment, and solution suggestions are covered.
Keywords: Sustainable agriculture; stubble; stubble burning; environmental pollution